Biologics and risk of tuberculosis in autoimmune rheumatic diseases: A real‐world clinical experience from India. (30th August 2018) - Shobha, Vineeta; Chandrashekara, S.; Rao, Vijay; Desai, Anu; Jois, Ramesh; Dharmanand, Balebail G.; Kumar, Sharath; Kumar, Pradeep; Dharmapalaiah, Chethana; Mahendranath, Kurugodu Mathada; Prasad, Shiva; Daware, Manisha Ashwin; et al.
Abstract: Aim: Tuberculosis (TB) is one of the major adverse events of concern associated with the use of biologics for managing autoimmune inflammatory rheumatic diseases (AIRDs). The study presents the data on incidence of TB in relation to biologic used, screening test and TB prophylaxis in a real‐world setting. Methods: The cross‐sectional, observational, retrospective study was conducted across 12 centres in Karnataka, India. The study included patients receiving biologics therapy for AIRDs, established based on the respective diagnostic criteria. The development of TB after receiving biologic therapy and other clinical variables and the predictability of the test performed for latent TB were evaluated. Results: One hundred and ninety‐five AIRDs patients with an average age of 41 years were initiated on biologic therapy. Twenty‐one patients were latent TB positive and were given antitubercular prophylaxis, prior to biologics treatment. During follow‐up, seven patients belonging to the negative test group (n = 174) developed TB. The negative predictive values noted for Mantoux test (n = 120) and quantiFERON TB gold test (n = 178) were 96.52% and 96.25%, respectively. Patients on anti‐tumor necrosis factor were more likely to develop TB. Presence of comorbidities and steroid use increased the likelihood of developing TB by 1.5 and 4.6 times, respectively. Conclusion: Close monitoring of patients receiving biologics is essential for early identification of adverse events, especially in test negative patients. Prophylaxis can effectively reduce the risk of developing TB in patients positive for screening.